2013
DOI: 10.3389/fneur.2013.00161
|View full text |Cite
|
Sign up to set email alerts
|

Tau in MAPK Activation

Abstract: The nature of “toxic” tau in Alzheimer’s disease (AD) has been unclear. During pathogenesis, the importance of tau oligomerization vs. tau phosphorylation is controversial and the investigation of both remains critical toward defining the “toxicity” of tau. The phosphorylation of tau on serines and/or threonines occurs early in the disease course and altering phosphorylation has been shown to disrupt neuropathogenesis. We have recently reported that in PC12-derived cells, tau had a role in signal transduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…This is consistent with previous literature that alterations in tau phosphorylation are a necessary component of NGF-induced neurite outgrowth and proliferation via MAPK signaling (Leugers, et al, 2013; Leugers and Lee, 2010), suggesting a role for the phosphorylation to contribute to the reductions in adult neurogenesis. However, the particular signaling cascades are unknown.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous literature that alterations in tau phosphorylation are a necessary component of NGF-induced neurite outgrowth and proliferation via MAPK signaling (Leugers, et al, 2013; Leugers and Lee, 2010), suggesting a role for the phosphorylation to contribute to the reductions in adult neurogenesis. However, the particular signaling cascades are unknown.…”
Section: Discussionsupporting
confidence: 93%
“…Should a reduction in pS214‐tau density signal a loss‐of‐function event, its absence from the subsynaptic domain may be particularly important to synaptic stability mechanisms. Specifically, tau within the subsynaptic domain is both strategically positioned to directly bind the actin cytoskeleton, and to participate in intracellular signaling cascades critical for actin remodeling, for example, the MAPK pathway (Cabrales Fontela et al, ; Frandemiche et al, ; He et al, ; Leugers, Koh, Hong, & Lee, ; Yamauchi & Purich, ). Notably, the interaction between tau and actin leads to accumulation of actin within mouse cortical neuron synapses (Frandemiche et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence that reactivation of the cell cycle induces tau phosphorylation is provided by two studies: McShea and colleagues [55] demonstrate that cell cycle induction in vitro induces tau phosphorylation, while Park and colleagues [54] demonstrate that cell cycle induction in vivo induces NFT and amyloid deposits. More recently, it has been demonstrated that specific phosphorylation of tau (Thr231) can promote MAPK activation in PC12 cells, which in turn could (further) activate the cell cycle reentry mechanisms in neurons [127, 128]. …”
Section: Evidence That the Differential Regulation Of Aβpp Processingmentioning
confidence: 99%